Graphite negative electrode material and preparation method thereof, and secondary battery

By adopting a double-layer clad structure on the graphite negative electrode material, combining the hydrophobic carbon-silicon composite layer and the hydrophilic polymer composite layer, the problems of clad shedding and insufficient conductivity are solved, and high-performance applications in aqueous electrolytes are achieved.

CN119695107APending Publication Date: 2025-03-25GUANGDONG KAIJIN NEW ENERGY TECH CORP LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411850559.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials have problems such as falling off during battery circulation, difficulty in controlling the dispersion of conductive agents, and poor performance in aqueous electrolytes.

Method used

A double-layer clad structure is adopted, the inner layer is a hydrophobic carbon-silicon composite layer and the outer layer is a hydrophilic polymer composite layer. The two are connected by -NH- or -CONH-combined bonds to enhance the bonding strength of the clad layer and introduce carbon nanotubes to improve conductivity and structural strength.

Benefits of technology

It effectively solves the problem of cladding shedding, improves conductivity and structural stability, is suitable for aqueous electrolytes, and improves the dynamic performance of secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190457410000161
    Figure BDA0005190457410000161
  • Figure BDA0005190457410000171
    Figure BDA0005190457410000171
  • Figure BDA0005190457410000172
    Figure BDA0005190457410000172
Patent Text Reader

Abstract

The invention provides a graphite negative electrode material, a preparation method thereof and a secondary battery. The graphite negative electrode material comprises a graphite inner core, a hydrophobic carbon-silicon composite layer and a hydrophilic polymer composite layer from inside to outside. The hydrophobic carbon-silicon composite layer and the hydrophilic polymer composite layer are connected through-NH-or-CONH-chemical bonds. And the hydrophobic carbon-silicon composite layer comprises a carbon layer containing carbon nanotubes and nano SiO2. The hydrophilic polymer composite layer comprises a carbon nanotube and a hydrophilic polymer. The coating layer of the graphite negative electrode material has relatively high bonding strength and can effectively resist stress generated in a battery circulation process and permeation influence of electrolyte so as to prevent the coating layer from falling off. In addition, the graphite negative electrode material has relatively high conductivity, and the content of the conductive agent can be reduced so as to avoid agglomeration in the pulping process of the too high conductive agent. The graphite negative electrode material has hydrophilicity, can be applied to a non-aqueous electrolyte and an aqueous electrolyte, and has a wide application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon material preparation, and in particular to a graphite negative electrode material and a preparation method thereof, and a secondary battery. Background Art

[0002] In the field of negative electrode materials for lithium-ion batteries, graphite is widely used due to its high theoretical specific capacity, low lithium insertion potential, good conductivity and stability. In order to improve the performance of graphite negative electrode materials to match the market demand for high capacity, safety and fast charging, although the industry has come up with a variety of technologies to improve graphite, there are still some problems.

[0003] First, many studies have been devoted to developing various coating layers to improve the performance of graphite negative electrode materials in batteries. However, there are many problems with the coating layers in the prior art. For example, some coating layers have weak structural strength. During the battery charging and discharging process, the volume of graphite changes, which easily causes the coating layer to fall off. Specifically, in the traditional coating structure, it is difficult to withstand the stress generated during the battery cycle by relying only on simple physical adsorption or weak chemical bonding. In addition, when certain chemical deposition methods are used for coating, although it may improve the tolerance of graphite to the electrolyte to a certain extent, the strengthening of the bonding force between the coating layer and the graphite is often ignored, so that the coating layer gradually peels off during long-term use, thereby affecting the cycle life and performance stability of the battery. In addition, for the application of graphite negative electrode materials in aqueous electrolyte systems, the existing coating structure is difficult to take into account both good hydrophilicity and structural stability at the same time, which makes the material's dispersibility in aqueous electrolytes limited, and the improvement of the battery's dynamic performance is limited.

[0004] Secondly, in terms of improving conductivity, most existing technologies use the method of adding conductive agents, but the dispersion of conductive agents in the system is difficult to control accurately and agglomeration is prone to occur, resulting in poor conductive effect.

[0005] Therefore, it is particularly important to find a graphite negative electrode material with better coating performance, better conductivity, and the ability to match aqueous electrolytes in order to expand its application range. Summary of the invention

[0006] Based on the above problems, the object of the present invention is to provide a graphite negative electrode material and a preparation method thereof, and a secondary battery. The coating layer of the graphite negative electrode material has a high bonding strength, which can effectively resist the stress generated during the battery cycle and the penetration of the electrolyte to prevent it from falling off. In addition, the graphite negative electrode material has a high conductivity, and the content of the conductive agent can be reduced to avoid agglomeration during the slurrying process of the excessive conductive agent. The graphite negative electrode material is hydrophilic and can be used not only in non-aqueous electrolytes but also in aqueous electrolytes, and has a wide range of application value.

[0007] To achieve the above-mentioned purpose, the first aspect of the present invention provides a graphite negative electrode material, comprising a graphite core, a hydrophobic carbon-silicon composite layer and a hydrophilic polymer composite layer from the inside to the outside, wherein the hydrophobic carbon-silicon composite layer and the hydrophilic polymer composite layer are connected by -NH- or -CONH- bonds, the hydrophobic carbon-silicon composite layer comprises a carbon layer containing carbon nanotubes and nano-SiO2, and the hydrophilic polymer composite layer comprises carbon nanotubes and a hydrophilic polymer.

[0008] The graphite negative electrode material of the present invention adopts a double-layer coating method, wherein the inner coating layer is a hydrophobic carbon silicon composite layer, and the outer coating layer is a hydrophilic polymer composite layer, and the two are connected by -NH- or -CONH- chemical bonds, which greatly enhances the bonding strength of the coating layer structure and can effectively solve the problem of coating layer shedding during battery use. Carbon nanotubes are introduced into both the inner and outer coating layers, which not only improves the structural strength of the overall coating layer, but also improves the conductivity of the material, and can reduce the content of the conductive agent to avoid agglomeration during the slurrying process of the excessive conductive agent. The outer coating layer is hydrophilic, so the double-layer coating structure of the graphite negative electrode material can not only maintain the stability of the structure, but also take into account good hydrophilicity at the same time, and has good contact with the aqueous electrolyte, so it can play a good role in the dynamic performance of the aqueous electrolyte secondary battery. The inner coating layer is a hydrophobic carbon-silicon composite layer. The carbon layer containing carbon nanotubes and nano-SiO2 is arranged on the surface of the graphite core, which can enhance the structural strength of the material. In addition, the inner coating layer can effectively prevent the solvent molecules and carbonate solvents in the electrolyte from excessively penetrating into the interior of the graphite core, so as to avoid damage to the overall structure of the graphite negative electrode material.

[0009] As a technical solution of the present invention, the surface of the hydrophilic polymer composite layer has hydrophilic groups, and the hydrophilic groups are amino groups, carboxyl groups or hydroxyl groups.

[0010] As a technical solution of the present invention, the hydrophilic group can be obtained by plasma treating the surface of the hydrophilic polymer composite layer.

[0011] As a technical solution of the present invention, the thickness of the hydrophobic carbon-silicon composite layer is 30 to 2000 nm.

[0012] As a technical solution of the present invention, the surface water contact angle of the hydrophobic carbon-silicon composite layer is 90 to 180°.

[0013] As a technical solution of the present invention, the thickness of the hydrophilic polymer composite layer is 30 to 2000 nm.

[0014] As a technical solution of the present invention, the surface water contact angle of the hydrophilic polymer composite layer is 0 to 90°.

[0015] As a technical solution of the present invention, the Dv50 of the graphite negative electrode material is 2 to 40 μm.

[0016] As a technical solution of the present invention, the carbon content of the graphite negative electrode material is ≥99%.

[0017] As a technical solution of the present invention, the specific surface area of ​​the graphite negative electrode material is 1 to 15 m 2 / g.

[0018] As a technical solution of the present invention, the compaction density of the graphite negative electrode material is 1.0-2.0 g / cm 3 .

[0019] As a technical solution of the present invention, the peeling strength of the graphite negative electrode material is ≥10M / m.

[0020] As a technical solution of the present invention, the conductivity of the graphite negative electrode material is ≥4.0×10 3 S / cm.

[0021] As a technical solution of the present invention, the charge transfer resistance of the graphite negative electrode material is 11.0 to 14.0Ω.

[0022] As a technical solution of the present invention, the 0.1C first charge capacity of the graphite negative electrode material is ≥340 mAh / g.

[0023] As a technical solution of the present invention, the first coulombic efficiency of the graphite negative electrode material at 0.1C is ≥90%.

[0024] As a technical solution of the present invention, the capacity retention rate of the graphite negative electrode material after 500 cycles at 0.1C is ≥95%.

[0025] A second aspect of the present invention provides a method for preparing a graphite negative electrode material, comprising the steps of:

[0026] (I) pre-treating graphite and chemically vapor depositing a hydrophobic carbon-silicon composite layer on the surface, wherein the raw materials for preparing the hydrophobic carbon-silicon composite layer include an organic carbon source, carbon nanotubes, nano-SiO2 and a catalyst,

[0027] (II) introducing amino groups into the surface of the hydrophobic carbon-silicon composite layer by a first plasma treatment to obtain a graphite mixture;

[0028] (III) preparing a hydrophilic polymer solution containing a first hydrophilic group, immersing the graphite mixture in the hydrophilic polymer solution, and reacting the amino group with the first hydrophilic group to obtain double-coated graphite, wherein the first hydrophilic group is a carboxyl group or a hydroxyl group;

[0029] (IV) washing and drying the double-coated graphite.

[0030] The preparation method of the present invention first vapor-deposits a hydrophobic carbon-silicon composite layer on the surface of graphite, and then introduces amino groups on the surface. After the hydrophilic polymer solution coats the graphite mixture, its hydrophilic group reacts with the amino group, so that the hydrophobic carbon-silicon composite layer and the hydrophilic polymer composite layer are connected through -NH- or -CONH- chemical bonds, thereby greatly enhancing the bonding strength of the double-layer coating structure. Then, washing and drying are performed to remove unreacted substances and impurities, thereby obtaining a graphite negative electrode material coated with a double layer of a hydrophobic carbon-silicon composite layer and a hydrophilic polymer composite layer.

[0031] As a technical solution of the present invention, the organic carbon source is at least one of methane, ethane, propane, acetylene, ethylene, propylene, n-butene, isobutene, n-butane and isobutane.

[0032] As a technical solution of the present invention, the mass ratio of the organic carbon source, the carbon nanotubes, the nano-SiO2 and the catalyst is 10-20:1-3:3-5:0.5-1.0.

[0033] As a technical solution of the present invention, the catalyst is a transition metal element.

[0034] As a technical solution of the present invention, the temperature of the chemical vapor deposition is 800-1200°C.

[0035] As a technical solution of the present invention, the pretreatment includes cleaning the surface of the graphite.

[0036] As a technical solution of the present invention, the graphite is artificial graphite.

[0037] As a technical solution of the present invention, the power of the first plasma treatment is 50 to 200 W, and the time is 30 to 180 seconds.

[0038] As a technical solution of the present invention, the concentration of the hydrophilic polymer solution is 5 to 15 wt.%.

[0039] As a technical solution of the present invention, the reaction temperature in step (III) is 10-50° C. and the reaction time is 1-10 h.

[0040] As a technical solution of the present invention, the washing solvent is water and / or ethanol.

[0041] As a technical solution of the present invention, the number of washings is 1 to 5.

[0042] As a technical solution of the present invention, the drying temperature is 40 to 80° C. and the drying time is 2 to 8 hours.

[0043] As a technical solution of the present invention, the hydrophilic polymer solution includes a hydrophilic polymer, carbon nanotubes and water, and the mass ratio of the hydrophilic polymer, the carbon nanotubes and the water is 3-15:0.5-4.0:85-95.

[0044] As a technical solution of the present invention, the hydrophilic polymer includes polyvinyl alcohol, polyacrylic acid or polyethylene glycol.

[0045] As a technical solution of the present invention, before step (IV), the surface of the double-coated graphite is treated with a second plasma to introduce a second hydrophilic group, wherein the second hydrophilic group is an amino group, a carboxyl group or a hydroxyl group.

[0046] The third aspect of the present invention provides a secondary battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the negative electrode material comprises the aforementioned graphite negative electrode material or the graphite negative electrode material prepared by the aforementioned graphite negative electrode material preparation method, and the electrolyte is an aqueous electrolyte or a non-aqueous electrolyte. DETAILED DESCRIPTION

[0047] The graphite negative electrode material of the present invention can be applied to aqueous electrolytes or non-aqueous electrolytes. The electrochemical energy storage device used as an aqueous electrolyte can be an aqueous secondary battery or an aqueous electrochemical supercapacitor or a combination of the two. The aqueous secondary battery can be an aqueous lithium ion battery, a sodium ion battery, a potassium ion battery or a zinc ion battery. The electrochemical energy storage device used as a non-aqueous electrolyte can be a non-aqueous secondary battery. The non-aqueous secondary battery can be a secondary lithium ion battery or a secondary sodium ion battery using carbonate and / or carboxylate as a solvent. Since the graphite negative electrode material of the present invention is hydrophilic, it has good contact with the aqueous electrolyte, so that it can well exert its kinetic performance in the aqueous electrolyte secondary battery.

[0048] When the graphite negative electrode material of the present invention is used as a negative electrode material, it can be used alone or mixed with other negative electrode materials (such as natural graphite, soft carbon, hard carbon, silicon-carbon composite material, silicon-oxygen composite material, etc.). The graphite negative electrode material can be used in a secondary battery, which includes a positive electrode material, a negative electrode material and an electrolyte.

[0049] The graphite negative electrode material of the invention comprises, from inside to outside, a graphite core, a hydrophobic carbon-silicon composite layer and a hydrophilic polymer composite layer.

[0050] The hydrophobic carbon-silicon composite layer includes a carbon layer containing carbon nanotubes and nano-SiO2. The hydrophobicity of the carbon layer containing carbon nanotubes and nano-SiO2 can not only effectively prevent the excessive penetration of solvent molecules and carbonate solvents in the electrolyte into the inner part of the graphite core to avoid damage to the overall structure of the graphite negative electrode material, but also enhance the structural strength of the material. The carbon nanotubes contained in the carbon layer can also improve the conductivity of the material. The thickness of the hydrophobic carbon silicon composite layer is 30 to 2000 nm. In one technical solution, the thickness of the hydrophobic carbon silicon composite layer is 100 to 1500 nm, or 500 to 1000 nm. As an example, the thickness can be, but is not limited to, 30 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm, 1500 nm, 1600 nm, 1700 nm, 1800 nm, 1900 nm, 2000 nm. The surface water contact angle of the hydrophobic carbon silicon composite layer is 90 to 180°. In one technical solution, the surface water contact angle is 100 to 160°, or 100 to 140°. As an example, the surface water contact angle may be, but is not limited to, 90°, 100°, 110°, 120°, 130°, 140°, 150°, 160°, 170°, 180°.

[0051] The hydrophilic polymer composite layer includes carbon nanotubes and hydrophilic polymers. As an outer coating layer, the hydrophilic polymer composite layer has good hydrophilicity and good contact with the aqueous electrolyte, so it can play a good role in the dynamic performance of the aqueous electrolyte secondary battery. The thickness of the hydrophilic polymer composite layer is 30 to 2000nm. In a technical solution, the thickness of the hydrophobic carbon silicon composite layer is 100 to 1500nm, or 500 to 1000nm. As an example, the thickness can be but not limited to 30nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm, 2000nm. The surface water contact angle of the hydrophilic polymer composite layer is 0-90°. In one technical solution, the surface water contact angle is 15-75°, or 30-60°. As an example, the surface water contact angle can be, but is not limited to, 0°, 10°, 10°, 20°, 30°, 40°, 50°, 60°, 70°, 80°, 90°.

[0052] By plasma treating the surface of the hydrophilic polymer composite layer, hydrophilic groups can be formed on the surface, and the hydrophilic groups are amino groups, carboxyl groups or hydroxyl groups. The amino groups on the surface of the hydrophobic carbon silicon composite layer and the hydrophilic groups on the surface of the hydrophilic polymer composite layer react and connect through -NH- or -CONH- bonds. The hydrophobic carbon silicon composite layer and the hydrophilic polymer composite layer are connected by chemical bonds, which can greatly enhance the bonding strength of the coating structure and effectively solve the problem of coating shedding during battery use.

[0053] The Dv50 of the graphite negative electrode material is 2 to 40 μm. In one technical solution, Dv50 is 5 to 30 μm, or Dv50 is 7 to 15 μm. As an example, it can be but is not limited to 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, and 40 μm. The carbon content of the graphite negative electrode material is ≥99%. In one technical solution, the carbon content is ≥99.9%. As an example, it can be but not limited to 99.0%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, 99.91%, 99.92%, 99.93%, 99.94%, 99.95%, 99.96%, 99.97%, 99.98%, 99.99%. The specific surface area of ​​the graphite negative electrode material is 1 to 15 m 2 / g, in one technical solution, the specific surface area is 1 to 10m 2 / g, or 1 to 5 m 2 As an example, the specific surface area may be, but is not limited to, 1 m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g. The compaction density of graphite negative electrode material is 1.0~2.0g / cm 3 In one technical solution, the compacted density is 1.1 to 1.8 g / cm 3 , or 1.2~1.7g / cm 3 As an example, the compaction density of the graphite negative electrode material may be, but is not limited to, 1.0 g / cm 3, 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 The peel strength of the graphite negative electrode material is ≥10M / m. In one technical solution, the peel strength is ≥30M / m or the peel strength is ≥60M / m. As an example, the peel strength of the graphite negative electrode material can be, but is not limited to, 10M / m, 20M / m, 30M / m, 40M / m, 50M / m, 60M / m, 70M / m, 80M / m. The conductivity of the graphite negative electrode material is ≥4.0×10 3 S / cm, as an example, can be but not limited to 4.0×10 3 S / cm, 4.1×10 3 S / cm, 4.2×10 3 S / cm, 4.3×10 3 S / cm, 4.4×10 3 S / cm, 4.5×10 3 S / cm. The electrical conductivity of the graphite negative electrode material of the present invention is relatively high, so when preparing the negative electrode plate, the content of the conductive agent can be reduced to less than 5% (the proportion of the sum of the mass of the negative electrode active material, the binder and the conductive agent). The charge transfer resistance of the graphite negative electrode material is 11.0 to 14.0Ω. As an example, it can be but not limited to 11.0Ω, 12.0Ω, 13.0Ω, and 14.0Ω. The 0.1C first charge capacity of the graphite negative electrode material is ≥340mAh / g. As an example, it can be but not limited to ≥340mAh / g, ≥350mAh / g, ≥355mAh / g, ≥360mAh / g, ≥365mAh / g, ≥370mAh / g, ≥375mAh / g, ≥380mAh / g, ≥385mAh / g, and ≥390mAh / g. The first coulombic efficiency of the graphite negative electrode material at 0.1C is ≥90%, as an example, it can be but not limited to ≥90%, ≥91%, ≥92%, ≥93%, ≥94%, ≥95%. The capacity retention rate of the graphite negative electrode material after 500 cycles at 0.1C is ≥95%, as an example, it can be but not limited to ≥95%, ≥96%, ≥97%, ≥98%, ≥99%.

[0054] The preparation method of the graphite negative electrode material of the present invention comprises the following steps: (I) pre-treating graphite and chemically vapor depositing a hydrophobic carbon-silicon composite layer on the surface; (II) introducing amino groups into the surface of the hydrophobic carbon-silicon composite layer by a first plasma treatment to obtain a graphite mixture; (III) preparing a hydrophilic polymer solution containing a first hydrophilic group, immersing the graphite mixture in the hydrophilic polymer solution and reacting the amino groups with the first hydrophilic group to obtain double-coated graphite; and (IV) washing and drying the double-coated graphite.

[0055] Wherein, in step (I), graphite is artificial graphite. Graphite can be pretreated before chemical vapor deposition, and the pretreatment includes cleaning the surface of graphite. Further, methods such as ultrasonic cleaning can be used to remove impurities and oil stains on the surface of graphite to ensure that its surface is clean and has suitable reactivity. The raw materials for preparing the hydrophobic carbon-silicon composite layer include organic carbon sources, carbon nanotubes, nano-SiO2 and catalysts. The organic carbon source is at least one of methane, ethane, propane, acetylene, ethylene, propylene, n-butene, isobutylene, n-butane and isobutane. The catalyst is a transition metal element, further a transition metal nickel, a transition metal palladium, a transition metal cobalt, etc. The mass ratio of the organic carbon source, carbon nanotubes, nano-SiO2 and catalyst is 10-20:1-3:3-5:0.5-1.0. As an example, it can be but not limited to 10:2:4:0.5, 10:2:4:0.8, 10:2:4:1.0, 10:2:5:0.5, 10:2:5:0.8, 10:2:5:1.0, 10:1:4:0.5, 10:1:4:0.8, 10:1:4:1.0, 18:2:4:0.5, 18:2:4:0.8, 18:2:4:1.0, 18:2:5:0.5, 18:2:5:0.8, 18:2:5:1.0, 18:1:4:0.5, 18:1:4:0.8, 18:1:4:1.0. The temperature of chemical vapor deposition is 800-1200° C., for example, it can be, but not limited to, 800° C., 850° C., 900° C., 950° C., 1000° C., 1050° C., 1100° C., 1150° C., 1200° C. Under the action of the deposition temperature and transition metal catalyst, the organic carbon source decomposes and deposits a uniform thin layer on the graphite surface together with the carbon nanotubes and the hydrophobic nano-SiO2, which is the aforementioned hydrophobic carbon-silicon composite layer. The time of chemical vapor deposition is controlled so that the thickness of the thin layer is 30-2000 nm.

[0056] The power of the first plasma treatment in step (II) is 50 to 200 W, and as an example, it can be but not limited to 50 W, 70 W, 90 W, 100 W, 120 W, 140 W, 160 W, 180 W, and 200 W. The time of the first plasma treatment is 30 to 180 s, and as an example, it can be but not limited to 30 s, 50 s, 70 s, 90 s, 100 s, 120 s, 140 s, 160 s, and 180 s. The first plasma treatment can be carried out using a plasma generator, and the operation of the first plasma treatment can refer to the conventional plasma treatment method, and amino groups are introduced into the surface of the hydrophobic carbon-silicon composite layer by the first plasma treatment.

[0057] In step (III), the hydrophilic polymer solution includes a hydrophilic polymer, carbon nanotubes and water, and the mass ratio of the hydrophilic polymer to the carbon nanotubes and the water is 3-15:0.5-4.0:85-95, and as an example, it can be but not limited to 3:0.5:85, 3:0.5:90, 3:0.5:95, 3:1.5:85, 3:1.5:90, 3:1.5:95, 3:3.0:85, 3:3.0:90, 3:3.0:95, 8:0 .5:85, 8:0.5:90, 8:0.5:95, 8:1.5:85, 8:1.5:90, 8:1.5:95, 8:3.5:85, 8:3.5:90, 8:3.5:95, 15:0.5:85, 15:0.5:90, 15:0.5:95, 15:1.5:85, 15:1.5:90, 15:1.5:95, 15:4.0:85, 15:4.0:90, 15:4.0:95. The hydrophilic polymer includes polyvinyl alcohol, polyacrylic acid or polyethylene glycol, so the hydrophilic polymer has a first hydrophilic group, and the first hydrophilic group is a carboxyl group or a hydroxyl group. The concentration of the hydrophilic polymer solution is 5-15wt.%, and as an example, it can be but not limited to 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%. The temperature at which the amino groups on the surface of the hydrophobic carbon silicon composite layer and the hydrophilic groups on the surface of the hydrophilic polymer composite layer react is 10-50°C, and as an example, it can be but not limited to 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C. The reaction time is 1-10h, and as an example, it can be but not limited to 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h.

[0058] Furthermore, the surface of the double-coated graphite can be treated with a second plasma to introduce a second hydrophilic group, wherein the second hydrophilic group is an amino group, a carboxyl group or a hydroxyl group. The introduction of the second hydrophilic group can increase the hydrophilicity of the graphite negative electrode material.

[0059] The washing solvent in step (IV) is water and / or ethanol, and the number of washings is 1 to 5, and as an example, it can be but not limited to 1 time, 2 times, 3 times, 4 times or 5 times. The drying temperature is 40 to 80°C, and as an example, the temperature can be but not limited to 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C. The drying time is 2 to 8h, and as an example, the time can be but not limited to 2h, 3h, 4h, 5h, 6h, 7h, 8h.

[0060] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0061] Example 1

[0062] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.

[0063] (I) Artificial graphite is treated with ultrasound to remove impurities and oil stains on the surface of the artificial graphite. Chemical vapor deposition is used, methane is used as a carbon source, carbon nanotubes, hydrophobic nano-SiO and a catalyst are added (the mass ratio of methane, carbon nanotubes, hydrophobic nano and catalyst is 15:2:4:0.8), and at a high temperature of 800°C and a transition metal nickel catalyst (accounting for 0.1% of the mass of the artificial graphite), the carbon source is decomposed and a hydrophobic carbon-silicon composite layer is deposited on the surface of the artificial graphite together with the carbon nanotubes and hydrophobic nano-SiO.

[0064] (II) A plasma generator was used to introduce amino groups onto the surface of the hydrophobic carbon-silicon composite layer. The power of the plasma treatment was 50 W and the time was 30 s.

[0065] (III) preparing a hydrophilic polymer solution, which is a 5wt.% polyvinyl alcohol and 1wt.% carbon nanotube aqueous solution. Slowly adding the hydrophilic polymer solution to the artificial graphite with a hydrophobic carbon-silicon composite layer deposited on the surface and stirring evenly, and then placing it in a reaction environment at 30°C for 5 hours to allow the amino groups on the surface of the hydrophobic carbon-silicon composite layer to react with the hydroxyl groups of the polyvinyl alcohol, thereby obtaining double-coated graphite.

[0066] Hydroxyl groups were introduced into the surface of the double-coated graphite using a plasma generator, and the power of the plasma treatment was 50 W and the time was 30 s.

[0067] (IV) The product was filtered and washed three times with deionized water and ethanol until the filtrate was neutral, and then dried in a vacuum drying oven at a drying temperature of 80° C. for 5 h to remove moisture and obtain a graphite negative electrode material.

[0068] Example 2

[0069] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.

[0070] (I) Artificial graphite is treated with ultrasound to remove impurities and oil stains on the surface of the artificial graphite. Chemical vapor deposition is used, methane is used as a carbon source, carbon nanotube fibers, carbon nanotubes, hydrophobic nano-SiO and a catalyst are added (the mass ratio of methane, carbon nanotubes, hydrophobic nano-SiO and catalyst is 15:2:4:0.8), and at a high temperature of 800°C and a transition metal nickel catalyst (accounting for 0.1% of the mass of the artificial graphite), the carbon source is decomposed and a hydrophobic carbon-silicon composite layer is deposited on the surface of the artificial graphite together with the carbon nanotubes and hydrophobic nano-SiO.

[0071] (II) A plasma generator was used to introduce amino groups onto the surface of the hydrophobic carbon-silicon composite layer. The power of the plasma treatment was 50 W and the time was 30 s.

[0072] (III) preparing a hydrophilic polymer solution, which is a 10wt.% polyvinyl alcohol and a 1wt.% carbon nanotube aqueous solution. Slowly adding the hydrophilic polymer solution to the artificial graphite with a hydrophobic carbon-silicon composite layer deposited on the surface, stirring evenly, and then placing it in a reaction environment at 30°C for 5 hours to allow the amino groups on the surface of the hydrophobic carbon-silicon composite layer to react with the hydroxyl groups of the polyvinyl alcohol, thereby obtaining a double-coated graphite.

[0073] Hydroxyl groups were introduced into the surface of the double-coated graphite using a plasma generator, and the power of the plasma treatment was 50 W and the time was 30 s.

[0074] (IV) The product was filtered and washed three times with deionized water and ethanol until the filtrate was neutral, and then dried in a vacuum drying oven at a drying temperature of 80° C. for 5 h to remove moisture and obtain a graphite negative electrode material.

[0075] Example 3

[0076] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.

[0077] (I) Artificial graphite is treated with ultrasound to remove impurities and oil stains on the surface of the artificial graphite. Chemical vapor deposition is used, methane is used as a carbon source, carbon nanotube fibers, carbon nanotubes, hydrophobic nano-SiO and a catalyst are added (the mass ratio of methane, carbon nanotubes, hydrophobic nano-SiO and catalyst is 15:2:4:0.8), and at a high temperature of 800°C and a transition metal nickel catalyst (accounting for 0.1% of the mass of the artificial graphite), the carbon source is decomposed and a hydrophobic carbon-silicon composite layer is deposited on the surface of the artificial graphite together with the carbon nanotubes and hydrophobic nano-SiO.

[0078] (II) A plasma generator was used to introduce amino groups onto the surface of the hydrophobic carbon-silicon composite layer. The power of the plasma treatment was 100 W and the time was 30 s.

[0079] (III) preparing a hydrophilic polymer solution, which is a 5wt.% polyvinyl alcohol and 1wt.% carbon nanotube aqueous solution. Slowly adding the hydrophilic polymer solution to the artificial graphite with a hydrophobic carbon-silicon composite layer deposited on the surface and stirring evenly, and then placing it in a reaction environment at 30°C for 5 hours to allow the amino groups on the surface of the hydrophobic carbon-silicon composite layer to react with the hydroxyl groups of the polyvinyl alcohol, thereby obtaining double-coated graphite.

[0080] Hydroxyl groups were introduced into the surface of the double-coated graphite using a plasma generator, and the power of the plasma treatment was 100 W and the time was 30 s.

[0081] (IV) The product was filtered and washed three times with deionized water and ethanol until the filtrate was neutral, and then dried in a vacuum drying oven at a drying temperature of 80° C. for 5 h to remove moisture and obtain a graphite negative electrode material.

[0082] Example 4

[0083] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.

[0084] (I) Artificial graphite is treated with ultrasound to remove impurities and oil stains on the surface of the artificial graphite. Chemical vapor deposition is used, methane is used as a carbon source, carbon nanotubes, hydrophobic nano-SiO and a catalyst are added (the mass ratio of methane, carbon nanotubes, hydrophobic nano and catalyst is 15:2:4:0.8), and at a high temperature of 800°C and a transition metal nickel catalyst (accounting for 0.1% of the mass of the artificial graphite), the carbon source is decomposed and a hydrophobic carbon-silicon composite layer is deposited on the surface of the artificial graphite together with the carbon nanotubes and hydrophobic nano-SiO.

[0085] (II) A plasma generator was used to introduce amino groups onto the surface of the hydrophobic carbon-silicon composite layer. The power of the plasma treatment was 100 W and the time was 30 s.

[0086] (III) preparing a hydrophilic polymer solution, which is a 10wt.% polyvinyl alcohol and a 1wt.% carbon nanotube aqueous solution. Slowly adding the hydrophilic polymer solution to the artificial graphite with a hydrophobic carbon-silicon composite layer deposited on the surface, stirring evenly, and then placing it in a reaction environment at 30°C for 5 hours to allow the amino groups on the surface of the hydrophobic carbon-silicon composite layer to react with the hydroxyl groups of the polyvinyl alcohol, thereby obtaining a double-coated graphite.

[0087] Hydroxyl groups were introduced into the surface of the double-coated graphite using a plasma generator, and the power of the plasma treatment was 100 W and the time was 30 s.

[0088] (IV) The product was filtered and washed three times with deionized water and ethanol until the filtrate was neutral, and then dried in a vacuum drying oven at a drying temperature of 80° C. for 5 h to remove moisture and obtain a graphite negative electrode material.

[0089] Example 5

[0090] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.

[0091] (I) Artificial graphite is treated with ultrasound to remove impurities and oil stains on the surface of the artificial graphite. Chemical vapor deposition is used, methane is used as a carbon source, carbon nanotube fibers, carbon nanotubes, hydrophobic nano-SiO and a catalyst are added (the mass ratio of methane, carbon nanotubes, hydrophobic nano-SiO and catalyst is 15:2:4:0.8), and at a high temperature of 800°C and a transition metal nickel catalyst (accounting for 0.1% of the mass of the artificial graphite), the carbon source is decomposed and a hydrophobic carbon-silicon composite layer is deposited on the surface of the artificial graphite together with the carbon nanotubes and hydrophobic nano-SiO.

[0092] (II) A plasma generator was used to introduce amino groups onto the surface of the hydrophobic carbon-silicon composite layer. The power of the plasma treatment was 50 W and the time was 30 s.

[0093] (III) preparing a hydrophilic polymer solution, which is a 5wt.% polyvinyl alcohol and 1wt.% carbon nanotube aqueous solution. Slowly adding the hydrophilic polymer solution to the artificial graphite with a hydrophobic carbon-silicon composite layer deposited on the surface and stirring evenly, and then placing it in a reaction environment at 30°C for 5 hours to allow the amino groups on the surface of the hydrophobic carbon-silicon composite layer to react with the hydroxyl groups of the polyvinyl alcohol, thereby obtaining double-coated graphite.

[0094] (IV) The double-coated graphite was filtered and washed three times with deionized water and ethanol until the filtrate was neutral, and then dried in a vacuum drying oven at a drying temperature of 80° C. for 5 h to remove moisture and obtain a graphite negative electrode material.

[0095] Example 6

[0096] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.

[0097] (I) Artificial graphite is treated with ultrasound to remove impurities and oil stains on the surface of the artificial graphite. Chemical vapor deposition is used, ethylene is used as a carbon source, carbon nanotubes, hydrophobic nano-SiO and a catalyst are added (the mass ratio of ethylene, carbon nanotubes, hydrophobic nano and catalyst is 10:3:3:1.0), and under the action of a high temperature of 800°C and a transition metal palladium catalyst (accounting for 0.5% of the mass of the artificial graphite), the carbon source is decomposed and a hydrophobic carbon-silicon composite layer is deposited on the surface of the artificial graphite together with the carbon nanotubes and hydrophobic nano-SiO.

[0098] (II) A plasma generator was used to introduce amino groups onto the surface of the hydrophobic carbon-silicon composite layer. The power of the plasma treatment was 50 W and the time was 30 s.

[0099] (III) preparing a hydrophilic polymer solution, which is an aqueous solution of 8 wt.% polyacrylic acid and 3 wt.% carbon nanotubes. Slowly adding the hydrophilic polymer solution to the artificial graphite with a hydrophobic carbon-silicon composite layer deposited on the surface and stirring evenly, and then placing it in a reaction environment at 30° C. for 5 hours to allow the amino groups on the surface of the hydrophobic carbon-silicon composite layer to react with the hydroxyl groups of polyvinyl alcohol, thereby obtaining double-coated graphite.

[0100] Hydroxyl groups were introduced into the surface of the double-coated graphite using a plasma generator, and the power of the plasma treatment was 50 W and the time was 30 s.

[0101] (IV) The product was filtered and washed three times with deionized water and ethanol until the filtrate was neutral, and then dried in a vacuum drying oven at a drying temperature of 80° C. for 5 h to remove moisture and obtain a graphite negative electrode material.

[0102] Example 7

[0103] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.

[0104] (I) Artificial graphite is treated with ultrasound to remove impurities and oil stains on the surface of artificial graphite. Chemical vapor deposition is used, methane is used as a carbon source, carbon nanotube fibers, carbon nanotubes, hydrophobic nano-SiO and catalysts are added (the mass ratio of methane, carbon nanotubes, hydrophobic nano-SiO and catalyst is 15:2:4:0.8), and at a high temperature of 1000°C and a transition metal nickel catalyst (accounting for 0.3% of the mass of artificial graphite), the carbon source is decomposed and a hydrophobic carbon-silicon composite layer is deposited on the surface of artificial graphite together with carbon nanotubes and hydrophobic nano-SiO.

[0105] (II) A plasma generator was used to introduce amino groups onto the surface of the hydrophobic carbon-silicon composite layer. The power of the plasma treatment was 50 W and the time was 70 s.

[0106] (III) preparing a hydrophilic polymer solution, which is a 5wt.% polyvinyl alcohol and 1wt.% carbon nanotube aqueous solution. Slowly adding the hydrophilic polymer solution to the artificial graphite with a hydrophobic carbon-silicon composite layer deposited on the surface and stirring evenly, and then placing it in a reaction environment at 40°C for 8h to allow the amino groups on the surface of the hydrophobic carbon-silicon composite layer to react with the hydroxyl groups of the polyvinyl alcohol, thereby obtaining double-coated graphite.

[0107] Hydroxyl groups were introduced into the surface of the double-coated graphite using a plasma generator, and the power of the plasma treatment was 50 W and the time was 40 s.

[0108] (IV) The product was filtered and washed four times with deionized water and ethanol until the filtrate was neutral, and then dried in a vacuum drying oven at a drying temperature of 70° C. for 7 h to remove moisture and obtain a graphite negative electrode material.

[0109] Comparative Example 1

[0110] This comparative example is a method for preparing a graphite negative electrode material, which includes the following steps.

[0111] (I) Artificial graphite is treated with ultrasound to remove impurities and oil stains on the surface of the artificial graphite. Chemical vapor deposition is used, methane is used as a carbon source, carbon nanotube fibers, carbon nanotubes, hydrophobic nano-SiO and a catalyst are added (the mass ratio of methane, carbon nanotubes, hydrophobic nano-SiO and catalyst is 15:2:4:0.8), and at a high temperature of 800°C and a transition metal nickel catalyst (accounting for 0.1% of the mass of the artificial graphite), the carbon source is decomposed and a hydrophobic carbon-silicon composite layer is deposited on the surface of the artificial graphite together with the carbon nanotubes and hydrophobic nano-SiO.

[0112] (II) preparing a hydrophilic polymer solution, wherein the hydrophilic polymer solution is a 5wt.% polyvinyl alcohol and a 1wt.% carbon nanotube aqueous solution, slowly adding the hydrophilic polymer solution to the artificial graphite with a hydrophobic carbon-silicon composite layer deposited on the surface, stirring evenly, and then placing it in a reaction environment at 30°C for 5 hours, thereby obtaining double-coated graphite.

[0113] (III) The product was filtered and washed three times with deionized water and ethanol until the filtrate was neutral, and then dried in a vacuum drying oven at a drying temperature of 80° C. for 5 h to remove moisture and obtain a graphite negative electrode material.

[0114] Comparative Example 2

[0115] This comparative example is a method for preparing a graphite negative electrode material, which includes the following steps.

[0116] (I) Artificial graphite is treated with ultrasound to remove impurities and oil stains on the surface of the artificial graphite. Chemical vapor deposition is used, methane is used as a carbon source, carbon nanotubes, hydrophobic nano-SiO and a catalyst are added (the mass ratio of methane, carbon nanotubes, hydrophobic nano and catalyst is 15:2:4:0.8), and at a high temperature of 800°C and a transition metal nickel catalyst (accounting for 0.1% of the mass of the artificial graphite), the carbon source is decomposed and a hydrophobic carbon-silicon composite layer is deposited on the surface of the artificial graphite together with the carbon nanotubes and hydrophobic nano-SiO.

[0117] (II) The product was filtered and washed three times with deionized water and ethanol until the filtrate was neutral, and then dried in a vacuum drying oven at a drying temperature of 80° C. for 5 h to remove moisture and obtain a graphite negative electrode material.

[0118] Comparative Example 3

[0119] This comparative example is a method for preparing a graphite negative electrode material, which includes the following steps.

[0120] (I) Artificial graphite is treated with ultrasound to remove impurities and oil stains on the surface of the artificial graphite. A hydrophilic polymer solution is prepared, wherein the hydrophilic polymer solution is a 5wt.% polyvinyl alcohol and a 1wt.% carbon nanotube aqueous solution. The hydrophilic polymer solution is slowly added to the artificial graphite and stirred evenly, and then placed in a reaction environment at 30°C for 5 hours to obtain coated graphite.

[0121] A plasma generator was used to introduce hydroxyl groups on the surface of the coated graphite. The power of the plasma treatment was 50 W and the time was 30 s.

[0122] (II) The product was filtered and washed three times with deionized water and ethanol until the filtrate was neutral, and then dried in a vacuum drying oven at a drying temperature of 80° C. for 5 h to remove moisture and obtain a graphite negative electrode material.

[0123] Comparative Example 4

[0124] This comparative example is a method for preparing a graphite negative electrode material, which includes the following steps.

[0125] Artificial graphite was treated with ultrasound to remove impurities and oil stains on the surface of artificial graphite. Artificial graphite was filtered and washed three times with deionized water and ethanol until the filtrate was neutral, and then dried in a vacuum drying oven at a drying temperature of 80°C for 5 hours to remove moisture and obtain a graphite negative electrode material.

[0126] After the first coating and before the second coating, the surface water contact angle of the intermediate in the process of preparing the graphite negative electrode material of Examples 1 to 7 and Comparative Examples 1 to 4 was tested as the surface water contact angle of the inner coating layer. The surface water contact angle of the graphite negative electrode material prepared in Examples 1 to 7 and Comparative Examples 1 to 4 was tested as the surface water contact angle of the outer coating layer. If there is only a single coating layer, the surface water contact angle of the graphite negative electrode material prepared is used as the surface water contact angle of the coating layer.

[0127] The graphite negative electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were subjected to various performance tests. The test conditions are as follows. The test results are shown in Table 1.

[0128] Malvern laser particle size analyzer MS2000 was used for particle size testing.

[0129] The specific surface area of ​​the graphite negative electrode material was tested using a Microscope 3020 specific surface area analyzer.

[0130] The thickness of the coating layer was tested using a transmission electron microscope JEM-2100.

[0131] The surface water contact angle tester was used to test the water contact angle.

[0132] The carbon content was tested using a carbon-sulfur analyzer.

[0133] The compaction density was tested using the UTM7305 battery powder compaction density meter.

[0134] The peel strength tester HD-609A was used to perform the peel strength test.

[0135] Conductivity test was performed using a conductivity meter.

[0136] The charge transfer resistance was tested using a HIOKI IM3590 impedance analyzer.

[0137] The electrical performance of the graphite negative electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 was tested by a half-cell test method. The test method is: the graphite negative electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were mixed with polyvinylidene fluoride and Super-P in a mass ratio of 70:15:15, and an appropriate amount of N-methylpyrrolidone was added as a solvent to prepare a slurry, which was coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet. A metal lithium sheet was used as the counter electrode, and an electrolyte mixed with a 1 mol / L LiPF6 three-component mixed solvent according to EC:DMC:EMC=1:1:1 (v / v) was used, and a polypropylene microporous membrane was used as a diaphragm, and a CR2032 button battery was assembled in a glove box filled with an inert gas. The charge and discharge test of button cells was conducted on the battery test system of Blue Electric Electronics Co., Ltd. At room temperature, the cells were discharged at a constant current of 0.1C until the voltage reached 0.01V, then discharged at a constant current of 0.02C until the voltage reached 0.005V, and charged at a constant current of 0.1C until the voltage reached 1.5V. The capacity charged to 1.5V was the 0.1C first charge capacity, and the ratio of the first charge capacity to the first discharge capacity was the first coulomb efficiency. The capacity retention rate was calculated after 500 cycles, and the capacity retention rate was the ratio of the capacity at the 500th week to the capacity at the first week.

[0138] Table 1 Performance test results of graphite negative electrode materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4

[0139]

[0140]

[0141] Continued from the table above

[0142]

[0143] From the results in Table 1, it can be seen that the comprehensive performance of the graphite negative electrode materials of Examples 1 to 7 is better than that of Comparative Examples 1 to 4, especially the peel strength is significantly better than that of Comparative Examples 1 to 4. This is because the double coating layers in the graphite negative electrode materials of Examples 1 to 7 are connected by -NH- or -CONH- chemical bonds, and the connection of chemical bonds greatly enhances the bonding strength of the coating layer structure. In Comparative Examples 2 to 4, either no coating is performed or only a hydrophilic or hydrophobic single layer coating is performed, and the strength of the coating performance is very low, so the peel strength is not high. Although there are hydrophobic carbon silicon composite layers and hydrophilic polymer composite layers in Comparative Example 1, the two coating layers are simply superimposed and composited, and there is no chemical bond between them. The hydrophilic polymer composite layer is easy to fall off, so the peel strength is low.

[0144] Comparison of Examples 1 to 4 shows that increasing the plasma power or increasing the concentration of the hydrophilic polymer can improve the hydrophilicity of the material and increase the peel strength.

[0145] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A graphite negative electrode material, characterized in that: The invention comprises a graphite core, a hydrophobic carbon silicon composite layer and a hydrophilic polymer composite layer from inside to outside, wherein the hydrophobic carbon silicon composite layer and the hydrophilic polymer composite layer are connected via -NH- or -CONH- chemical bonds, the hydrophobic carbon silicon composite layer comprises a carbon layer containing carbon nanotubes and nano-SiO2, and the hydrophilic polymer composite layer comprises carbon nanotubes and a hydrophilic polymer.

2. The graphite negative electrode material according to claim 1, characterized in that The surface of the hydrophilic polymer composite layer has hydrophilic groups, and the hydrophilic groups are amino groups, carboxyl groups or hydroxyl groups.

3. The graphite negative electrode material according to claim 2, characterized in that: The hydrophilic group can be obtained by plasma treating the surface of the hydrophilic polymer composite layer.

4. The graphite negative electrode material according to any one of claims 1 to 3, characterized in that: The invention comprises at least one of the following features (i) to (xiv): (i) the thickness of the hydrophobic carbon-silicon composite layer is 30 to 2000 nm; (ii) the surface water contact angle of the hydrophobic carbon-silicon composite layer is 90 to 180°; (iii) the thickness of the hydrophilic polymer composite layer is 30 to 2000 nm; (iv) the surface water contact angle of the hydrophilic polymer composite layer is 0 to 90°; (V) The Dv50 of the graphite negative electrode material is 2 to 40 μm; (vi) The carbon content of the graphite negative electrode material is ≥ 99%; (VII) The specific surface area of ​​the graphite negative electrode material is 1 to 15 m 2 / g; (VIII) The compaction density of the graphite negative electrode material is 1.0 to 2.0 g / cm 3 ; (IX) The peel strength of the graphite negative electrode material is ≥10M / m; (10) The electrical conductivity of the graphite negative electrode material is ≥4.0×10 3 S / cm; (XI) The charge transfer resistance of the graphite negative electrode material is 11.0 to 14.0 Ω; (XII) The 0.1C first charge capacity of the graphite negative electrode material is ≥340 mAh / g; (XIII) The first coulombic efficiency of the graphite negative electrode material at 0.1C is ≥ 90%; (XIV) The capacity retention rate of the graphite negative electrode material after 500 cycles at 0.1C is ≥95%.

5. A method for preparing a graphite negative electrode material, characterized in that: Includes steps: (I) pre-treating graphite and chemically vapor depositing a hydrophobic carbon-silicon composite layer on the surface, wherein the raw materials for preparing the hydrophobic carbon-silicon composite layer include an organic carbon source, carbon nanotubes, nano-SiO2 and a catalyst, (II) introducing amino groups into the surface of the hydrophobic carbon-silicon composite layer by a first plasma treatment to obtain a graphite mixture; (III) preparing a hydrophilic polymer solution containing a first hydrophilic group, immersing the graphite mixture in the hydrophilic polymer solution, and reacting the amino group with the first hydrophilic group to obtain double-coated graphite, wherein the first hydrophilic group is a carboxyl group or a hydroxyl group; (IV) washing and drying the double-coated graphite.

6. The method for preparing a graphite negative electrode material according to claim 5, characterized in that: The invention comprises at least one of the following features (1) to (12): (1) The organic carbon source is at least one of methane, ethane, propane, acetylene, ethylene, propylene, n-butene, isobutene, n-butane and isobutane; (2) The mass ratio of the organic carbon source, the carbon nanotubes, the nano-SiO2 and the catalyst is 10-20:1-3:3-5:0.5-1.

0. (3) The catalyst is a transition metal element; (4) The temperature of the chemical vapor deposition is 800 to 1200° C.; (5) The pretreatment includes cleaning the surface of the graphite; (6) The graphite is artificial graphite; (7) The power of the first plasma treatment is 50 to 200 W, and the time is 30 to 180 s; (8) The concentration of the hydrophilic polymer solution is 5 to 15 wt.%; (9) The reaction temperature in step (III) is 10 to 50° C. and the reaction time is 1 to 10 h; (10) The washing solvent is water and / or ethanol; (11) The number of washing times is 1 to 5; (12) The drying temperature is 40 to 80° C. and the drying time is 2 to 8 hours.

7. The method for preparing a graphite negative electrode material according to claim 5, characterized in that: The hydrophilic polymer solution comprises a hydrophilic polymer, carbon nanotubes and water, and the mass ratio of the hydrophilic polymer, the carbon nanotubes and the water is 3-15:0.5-4.0:85-95.

8. The method for preparing a graphite negative electrode material according to claim 7, characterized in that: The hydrophilic polymer includes polyvinyl alcohol, polyacrylic acid or polyethylene glycol.

9. The method for preparing a graphite negative electrode material according to claim 7, characterized in that: Before step (IV), the surface of the double-coated graphite is treated with a second plasma to introduce a second hydrophilic group, wherein the second hydrophilic group is an amino group, a carboxyl group or a hydroxyl group.

10. A secondary battery comprising a positive electrode material, a negative electrode material and an electrolyte, characterized in that: The negative electrode material comprises the graphite negative electrode material according to any one of claims 1 to 4 or the graphite negative electrode material prepared by the method for preparing the graphite negative electrode material according to any one of claims 5 to 9, and the electrolyte is an aqueous electrolyte or a non-aqueous electrolyte.

Citation Information

Cited By

  • Preparation process of biomass-based carbon nanotube and natural graphite composite negative electrode material

    CN120389026A